ANALISIS EFISIENSI PEMASARAN UBI KAYU DI PROVINSI LAMPUNG - Anggraini, Nuni; Hasyim, Ali Ibrahim; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research aims to analyze the efficiency of cassava marketing system in Lampung Province. The research was conducted purposively in Lampung Tengah and Lampung Utara in May-June 2012. Farmer respondents were chosen randomly and marketing channel respondents were taken by tracing marketing networks. Data consisted of primary and secondary data. Data analysis included analysis of marketing system efficiency. The results showed that the marketing system of cassava in Lampung Province was efficient with producer share (Ps) of more than 80 %, with the following conditions: (a) the market structure was almost a perfect competition. (b) the market conduct: cassava farmers had no difficulty in marketing their product. (c) the market performance: there were two marketing channel; marketing margin and Profit Margin Ratio were relatively small, and the elasticity of price transmission was less than one.